A Vaspin–HSPA1L complex protects proximal tubular cells from organelle stress in diabetic kidney disease - Nakatsuka, Atsuko (Commun Biol, 2021)
Proximal tubular cells (PTCs) are crucial for maintaining renal homeostasis, and tubular injuries contribute to progression of diabetic kidney disease (DKD). However, the roles of visceral adipose tissue-derived serine protease inhibitor (vaspin) in the development of DKD is not known. We found vaspin maintains PTCs through ameliorating ER stress, autophagy impairment, and lysosome dysfunction in DKD. Vaspin−/− obese mice showed enlarged and leaky lysosomes in PTCs associated with increased apoptosis, and these abnormalities were also observed in the patients with DKD. During internalization into PTCs, vaspin formed a complex with heat shock protein family A (Hsp70) member 1 like (HSPA1L) as well as 78 kDa glucose-regulated protein (GRP78). Both vaspin-partners bind to clathrin heavy chain and involve in the endocytosis. Notably, albumin-overload enhanced extracellular release of HSPA1L and overexpression of HSPA1L dissolved organelle stresses, especially autophagy impairment. Thus, vapsin/HSPA1L-mediated pathways play critical roles in maintaining organellar function of PTCs in DKD.